2020
DOI: 10.1111/jdi.13229
|View full text |Cite
|
Sign up to set email alerts
|

Flash glucose monitoring in type 1 diabetes: A comparison with self‐monitoring blood glucose

Abstract: Aims/Introduction A flash glucose monitoring (FGM) system has become available. To clarify the relationship between FGM and self‐monitoring blood glucose (SMBG) values, we compared the two values after simultaneous measurement in Japanese patients with type 1 diabetes, under daily life settings. Materials and Methods A total of 20 outpatients with type 1 diabetes were analyzed. When FGM and SMBG were carried out simultaneously (within ±3 min), the values were adopted and each FGM value was matched and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In addition, CGM could not be carried out for every participant who started the administration of an SGLT2i. Furthermore, a previous study showed that CGM values were lower than SMBG values in the lower glucose range, and higher in the higher glucose range 23 . Capillary and venous glucose concentrations are similar under steady‐state conditions, but might differ under dynamic conditions 24 .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, CGM could not be carried out for every participant who started the administration of an SGLT2i. Furthermore, a previous study showed that CGM values were lower than SMBG values in the lower glucose range, and higher in the higher glucose range 23 . Capillary and venous glucose concentrations are similar under steady‐state conditions, but might differ under dynamic conditions 24 .…”
Section: Discussionmentioning
confidence: 97%
“…p-values < 0.05 were considered as statistically significant. Thieme Article tion, a recent publication by Babaya et al [26] showed that glucose values determined by system A were lower in the low glucose range, and higher in the high glucose range than corresponding SMBG values. Since the TbR < 54 and TbR < 70 of system A was about 25-50 % higher than that of system B, this could be a reason for the lower mean glucose and the correspondingly lower GMI value of system A and highlights the clinical relevance of differences in the accuracy of CGM systems, their derived metrics and the resulting decisions.…”
Section: Discussionmentioning
confidence: 98%
“…Because glycemic variability is a significant and independent determinant of hypoglycemia in patients with type 2 diabetes mellitus on insulin therapy 19 , once the dose of insulin or sulfonylurea has been adjusted appropriately, TBR should be rather decreased by the combination therapy through an improvement in glycemic variability 9 . Previous studies showed that CGM values were lower than self‐monitoring blood glucose values in the low glucose range 20 , and that capillary and venous glucose concentrations can differ under dynamic conditions 21 . Therefore, CGM data might not be highly accurate and the possibility of such inaccuracies should be considered, especially in the low glucose region.…”
Section: Discussionmentioning
confidence: 99%